2013
DOI: 10.1007/s13632-013-0087-3
|View full text |Cite|
|
Sign up to set email alerts
|

Metallography of Sputter-Deposited SS304+Al Coatings

Abstract: Plasma-enhanced magnetron sputtered coatings of 304 stainless steel (SS304)?Al containing nominally 0, 4, 7, and 10 wt% Al were deposited on SS304 substrates. The sputter-deposited coatings were characterized for their phase formation and grain size using x-ray diffraction, scanning electron microscopy, and transmission electron microscopy techniques. The sputter-deposited SS304 coatings with no Al contained the metastable phases a and r, while all other coatings that contained different levels of Al showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The tested specimens exhibit similar patterns that reveal the presence of Aluminium and Stainless steel metal. The sharp diffraction peaks correspond to the crystalline nature of Al1050 and SS304 layer [18][19][20][21][22][23][24] whereas diffused diffraction peaks correspond to the amorphous nature of the Adhesive layer [25]. The XRD test shows a sharp peak at an angle of 38 figure 1.…”
Section: Xrdmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested specimens exhibit similar patterns that reveal the presence of Aluminium and Stainless steel metal. The sharp diffraction peaks correspond to the crystalline nature of Al1050 and SS304 layer [18][19][20][21][22][23][24] whereas diffused diffraction peaks correspond to the amorphous nature of the Adhesive layer [25]. The XRD test shows a sharp peak at an angle of 38 figure 1.…”
Section: Xrdmentioning
confidence: 99%
“…The N is the number of reflections observed. The obtained texture coefficient TC(hkl) for the Al1050 sheet and SS304 sheet is 3.81(220) and 1.91 (102) [19][20][21][22][23][24][25]. The strain (ε) in the Al1050 and SS304 sheet utilised for the manufacturing of the Al1050/SS304 sandwich composite is determined by using equation…”
Section: Xrdmentioning
confidence: 99%
“…Magnetron-sputtering allows the covering of diverse substrate materials with protective superficial layers of different SS specifications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Films with thicknesses in the order of magnitude of 1.0 μm can be obtained straightforwardly on either heated or unheated substrates or as interlayers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Zhang et al 4 reported on the phase stability of SS films as a function of both target chemical composition and external substrate heating.…”
Section: Introductionmentioning
confidence: 99%